Development and application of bimetallic catalysts supported carbon nanotube for 1-propanol electrooxidation - Şefika Kaya (MANAS: Journal of Engineering)
Herein, carbon nanotube supported bimetallic catalysts (PtBi/CNT) are synthesized at various metals weight loadings by NaBH4 reduction method. The surface morphology and crystal structure of the catalysts are investigated via X-ray diffraction (XRD) and electron microscopy with energy dispersive X-ray (SEM-EDX) advance surface methods. According to XRD results, the crystal size of PtBi(90:10)/CNT catalyst is determined as 4.66 nm. Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and chronoamperometry (CA) electrochemical techniques are used to determine 1-propanol electrooxidation activities of the catalysts. The highest specific activity and mass activity are obtained with PtBi(90:10)/CNT catalyst as 5.663 mA/cm2 and 447.21 mA/mg Pt, respectively. However, it is concluded that PtBi(90:10)/CNT catalyst can be used as an anode catalyst in 1-propanol electrooxidation with long-term stability and low resistance.